Academia in Crisis The Rise and Risk of Neoliberal Education in Europe - Donskis, Leonidas; Sabelis, Ida; Kamsteeg, Frans; Wels, Harry (Value Inquiry Book Series, 2019)
This book dissects current commercial, capitalist and fast cultures in universities. It argues that there is no turning back, nor marching on. Under the present regimes ruling universities, all that is left is reflection on academic qualities and opting in, or out. Readership: All interested in contemporary developments in higher education, be it from a didactic, and international (European), or a human rights' perspective.